Unix and Linux - Ray, Deborah S.; Ray, Eric J.; Ray, Deborah S. (Berkeley, CA : Peachpit Press, 2009)
With Unix, 4th Edition: Visual QuickStart Guide readers can start from the beginning to get a tour of the Unix operating system, or look up specific tasks to learn just what they need to know. This task-based, visual reference guide uses step-by-step instructions and plenty of screenshots, and includes three years worth of new material based on the latest Unix developments. This reference guide details all Unix commands and options along with tips that put those commands in context. Leading Unix authorities Deborah S. Ray and Eric J. Ray leverage their expertise as technical writers and working in the industry (Sun Microsystems) as they take readers step-by-step through the most common Unix commands and options.
Getting Started with Unix -- Using Directories and Files -- Working with Your Shell -- Creating and Editing Files -- Controlling Ownership and Permissions -- Manipulating Files -- Getting Information -- Configuring Your Unix Environment -- Running Scripts and Programs -- Writing Basic Scripts -- Sending and Reading E-mail -- Accessing the Internet -- Working with Encoded and Compressed Files -- Using Handy Utilities -- Being Root -- Sensational Unix Tricks.
Includes index.
Previously published under title: UNIX, 3rd ed., 2006.
1
Keywords: UNIX; Linux; Operating systems (Computers)